Corona virus vaccine hesitancy among higher education students in Adama City, Oromia, Ethiopia - Abebe, Dawit; Mengistu, Tewodros; Demssie, Enku Afework; Mesfin, Sinetibeb (Frontiers in Public Health, 2024)
Background: Vaccination stands as the most efficient approach for managing the continued transmission of infections and preventing the emergence of novel variants.COVID-19 vaccine hesitancy poses a significant burden in the fight to achieve herd immunity.A cross-sectional study, based on institutional parameters, was undertaken among a cohort of 530 higher education students, selected via a simple random sampling. Study participants were selected using a systematic random sampling technique from Feb to Mar 2022. Structured questionnaire data were gathered and subsequently analyzed utilizing SPSS version 21. The strength of the association between various factors and COVID-19 vaccine hesitancy was assessed using the odds ratio along with its 95% confidence interval. Statistical significance was deemed present at a p-value of less than 0.05. The prevalence of coronavirus vaccine hesitancy was 47.5%. Residential address (AOR=2.398, 95%CI: 1.476 -3.896); agree with leaders and groups that do not support COVID-19 vaccination (AOR=2.292, 95%CI: 1.418-3.704); came from a community whose leaders support covid-19 vaccination for young adults (AOR=0.598, 95%CI: 0.381-0.940) and believe Covid-19 vaccines are safe (AOR=0.343,95%CI: 0.168-0.701) were found to be factors with a significant association with COVID-19 vaccine hesitancy. About five out of ten students who participated in this study are coronavirus vaccine-hesitant. Incorporating messages and initiatives into local plans to target the factors identified in this study specifically is imperative for substantially enhancing the COVID-19 vaccine uptake among students in higher education institutions.